(untitled) (Kronika Bydgoska, 2018)
The Chronicle of the Poznań Jesuits has not yet been fully used in the research on the history of Bydgoszcz. The purpose of this article was to describe direct references concerning Bydgoszcz featured on the pages of the chronicle, showing also its potential value in studies on the history of the city.